Ultrastaging of colon cancer by sentinel node biopsy using fluorescence navigation with indocyanine green - Hirche, Christoph (International journal of colorectal disease, 2012)
Purpose: Lymph node status is the most important prognostic factor in colon cancer, but the role of sentinel lymph node biopsy (SLNB) as a tool for identification of micrometastatic disease and extraanatomical lymph nodes for adjuvant strategies and a tailored approach still remains unclear. Indocyanine green (ICG) fluorescence detection is a new method for SLNB allowing real-time lymphography and lymph node detection. This study was designed to evaluate the feasibility of fluorescence-guided sentinel lymph node detection in colon carcinoma. Methods: Twenty six patients with colon adenocarcinoma were prospectively included in this study. Intraoperatively, a peritumorous injection with a mean of 2.0 ml ICG was performed, followed by lymphatic mapping and SLNB. Clinical feasibility, detection rate, and sensitivity of the method were analyzed. Results: No adverse reactions occurred due to the injection of ICG. Overall, ICG fluorescence imaging identified 1.7 sentinel lymph node (SLN) in average in 25 out of 26 patients (detection rate, 96%). Metastatic involvement of the SLN was found in nine out of 11 nodal positive patients by conventional histopathology. The sensitivity of the method was 82% for colon carcinoma, respectively. Conclusion: ICG fluorescence imaging is a new, feasible method for SLNB of colon carcinoma and enables ultrastaging with improved accuracy but with limited validity due to the small number of cases. One advantage of this technique is real-time visualization of lymphatic vessels and SLNB without radiation exposure. Further, larger series are necessary to analyze the role of fluorescence-guided SLNB for colon cancer.